The Geculan Bocah Dance Performance As A Creative Space for Children - Paranti, Lesa; Putri, Rimasari Pramesti; Pebrianti, Sestri Indah (Harmonia: Journal of Arts Research and Education, 2019)
This study aims to analyze the creativity of children (dancers) in the Geculan Bocah dance performance and how the performance becomes a space to arouse creativity. The case study in this research was the phenomenon of the Geculan Bocah dance performance in Sanggar Tanuwiyoyo Semarang Regency. The method used is a qualitative research method through a phenomenological approach. Data collection was done by using the method of observation, interviews, and documentation. The data analysis test used the Miles and Hubberman model through data reduction, data presentation, and drawing conclusions. Data validity used triangulation of sources, techniques, and methods. The results showed that Geculan Bocah dance performance consisted of 3 parts, namely the beginning, middle (core) and final (ending). Each part of the performance requires the creative role of the child as a dancer. Children’s creative roles include individual creativity, collaborative creativity, and communal creativity. Individual creativity attempts every child to show good performance. Collaborative creativity can be seen in the cohesiveness and togetherness during the show. The communal creativity arises because it is influenced by the audience and the atmosphere of the performance. The Geculan Bocah dance performance is a creative product, a creative space/ process, and a driver for the development of children’s creativity.